Cardiovascular drug shortages in Lebanon: A broken heart - Georges Khattar; Jennifer Hallit; Carolla El Chamieh; Elie Bou Sanayeh (Health Economics Review, 2022)
For nearly 3 years now, Lebanon has been assailed by compounded crises. With the economic instability, the coronavirus pandemic, and the explosion of the Beirut Port on August 4, 2020; the fragile Lebanese healthcare system has found itself at massive risk of a catastrophic public health crisis secondary to cardiovascular drug shortages. The time has come for public health authorities to find urgent solutions for this national trajedy that is projected to last for years.
Keywords: 330; Drug shortages; Pharmaceutical industry; Public health crisis